Management of acute acquired comitant esotropia using prisms and vision therapy - PremNandhini Satgunam; Rinki Gupta; Manali Sikder; Rohan Nalawade; Ramesh Kekunnaya (PLoS ONE, 2026)
Purpose Acute acquired comitant esotropia (AACE) once considered rare, is now becoming more prevalent. Surgery in these cases can get delayed when the strabismus angle varies or if the patient is unwilling. In such cases optical management and vision therapy can be considered. We present the outcomes of such management for AACE. Methods This retrospective study included a cohort of patients diagnosed with non-accommodative or non-neurological AACE, managed in our institute between January to October, 2023. Prisms were prescribed to patients experiencing constant double vision. All patients were given vision therapy exercises. Eso deviation and divergence range were measured pre and post therapy. Results Fourteen patients were included. Of these, 5 patients (with eso deviation ≤20PD) were relieved with vision therapy exercises alone. For the remaining 9 patients, prisms were prescribed along with vision therapy. Post-vision therapy, 2 patients could achieve binocular single vision without prisms, and in 4 patients the prism power was reduced. In the remaining 3, full prism correction was warranted, one of them opted for surgery. The median reduction in eso deviation by 6.5PD (range:2–25PD) and increase in divergence by 7PD (range:0–17PD) after vision therapy was significant (p < 0.03). Conclusion Non-surgical intervention reduced the eso deviation in 79% (11/14) of patients. Certain types of AACE seem to be amenable to vision therapy and/or optical management. Temporary Fresnel prisms can be considered in majority of these patients and tapered away later, if their divergence range can be improved with vision therapy.